SEPIC-based Harmonic Distortion Reduction in BLDC Motors - Dr B Mouli Chandra; Dr B Venkata Prasanth; Dr. G. Srinivasa Rao; Prof. B. Linga Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
— This study examines a novel drive method for BLDC motor speed regulation. In this mode, the line voltage waveform is observed while having both voltage and current. This allows us to deduce harmonics of lower order and, possibly, increase the cosine angle of voltage and current when neither voltage nor current sensor equipment is present. For driving a permanent magnet brushless dc (BLDC) motor with unipolar currents, a front-end SEPIC and a switch are proposed in series with each phase. One benefit of using lower voltage applications is that the supply voltage can be obtained for better current regulation. The SEPIC converter is built to work with an ac supply in the irregular conduction mode. The present topology is simulated and verified by using MATLAB/SIMULINK